Climate Cards: Interactive Educational Media on Climate Change for Elementary School Students - Setiadi, Wisnu (Indonesian Journal of Islamic Elementary Education, 2025)
Human activities are inevitably in harmony with climate change. Thus, the importance of preserving the environment must be instilled in the minds of future generations. This research aims to explore and describe the use of climate cards for elementary school children. This research also tries to identify creative actions that can increase awareness of climate change. This research used a qualitative-descriptive method. Data were collected by conducting a Focus Group Discussion. Data were then analyzed in each meeting to conclude. The results of the analysis showed that interactive educational media on climate change have not been widely used in SDN Jetis 2 Saptosari. The climate cards were not only used during the lecturing session. They encouraged students to be more collaborative, critical, and communicative in learning to support their cognitive, affective, and psychomotor abilities. The use of the climate cards could increase students' interest in learning about climate change issues, especially when they are assigned to create a poster about waste issues.